Varicocele Repair Prior to Assisted Reproductive Technology: Patient Selection and Special Considerations - Kohn, Jaden R (Res Rep Urol, 2020)
Clinical varicoceles are one of the most commonly identified physical exam abnormalities in men presenting with infertility. Clinical varicoceles can cause impaired spermatogenesis and surgical correction can improve semen parameters in select men. Increasingly, andrologists are performing varicocele repairs prior to intrauterine insemination (IUI), in vitro fertilization (IVF), and intracytoplasmic sperm injection (ICSI) to boost male fertility potential. In this review, we evaluated the available literature 1) to determine if varicocelectomy prior to IUI or assisted reproductive technologies proved to improve sperm production or pregnancy outcomes; and 2) to identify who may be the ideal candidate for pre-IUI/ART varicocelectomy. Overall, few studies have explored this topic and little can be concluded about the impact of varicocelectomy prior to IUI. The evidence, however, does support that correcting a clinical varicocele can increase pregnancy outcomes in couples who plan to pursue IVF or ICSI. When selecting patients for varicocelectomy prior to IUI or ART, clinicians should evaluate female age as improvement in semen parameters can take 6 months after varicocelectomy and this duration of time may be deleterious in cases of advanced maternal age when each cycle becomes increasingly important. Overall, the currently limited literature regarding clinical varicoceles correction demonstrates that pregnancy rates can be increased when comparing patients who have undergone varicocelectomy prior to ART with those who had clinical varicocele but did not undergo surgery.